2015
DOI: 10.3923/ajsr.2015.342.350
|View full text |Cite
|
Sign up to set email alerts
|

Development of Translucent Zirconia for Dental Crown Applications

Abstract: Zirconia-based dental ceramic is widely used for crown restoration, because of its superior mechanical properties and favorable biocompatibility. However, yttria-stabilized tetragonal zirconia (3YSZ), which is used in most dental crown restorations, has low translucency. This characteristic is unfavorable and results in low aesthetic quality of dental restoration. In this study, translucent 3YSZ dental ceramics were fabricated using nano-sized powder (20 nm) and high-temperature sintering (1500°C). The green b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Another explanation may be attribute to the scattering effect of the light as a result of the smaller particles size in Celtra press resulting in higher relative opacity when compared to e.max. 31 In current study, results showed that all samples L* values were decreased and a* and b* values were increased, indicating that decrease in brightness and tendency to become reddish and yellowish or to be darker after aging. These finding are similar to previous studies reported that ceramics get darker, reddish, or yellowish.…”
Section: Vasiliu Et Al (2020)supporting
confidence: 46%
See 1 more Smart Citation
“…Another explanation may be attribute to the scattering effect of the light as a result of the smaller particles size in Celtra press resulting in higher relative opacity when compared to e.max. 31 In current study, results showed that all samples L* values were decreased and a* and b* values were increased, indicating that decrease in brightness and tendency to become reddish and yellowish or to be darker after aging. These finding are similar to previous studies reported that ceramics get darker, reddish, or yellowish.…”
Section: Vasiliu Et Al (2020)supporting
confidence: 46%
“…18,22 Nevertheless, the main cause for color change of the resin-cemented laminate veneers was the resin cement itself, due to the internal discoloration of the resin composite luting agents by hydrolysis reaction while the ceramic has the lowest effect on discoloration. 31,36 This might explain why the aging process had a greater effect on the restoration side than the natural side, as the restoration side has many interfaces of ceramic, resin cement and tooth itself and all of them are liable to discoloration.…”
Section: Turgut Et Al (2011)mentioning
confidence: 99%